High-temperature-resistant ablative resorcinol-formaldehyde aerogel and preparation method thereof

CN117624713BActive Publication Date: 2026-10-27AEROSPACE INST OF ADVANCED MATERIALS & PROCESSING TECH
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202311495668.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-11-10
Publication Date
2026-10-27
Estimated Expiration
2043-11-10

AI Technical Summary

Technical Problem

[0005]为了改善上述改性酚醛-二氧化硅杂化气凝胶防/隔热性能及制备方法,本发明提供了一种耐高温烧蚀维形酚醛气凝胶及其制备方法,实现了酚醛与氧化铝纳米晶的有机无机杂化,弥补了酚醛-二氧化硅杂化气凝由于二氧化硅烧结导致维形性、隔热性不足的缺陷,能够满足长时高速飞行器对高速飞行器对热防护材料防/隔热一体化的要求

Benefits of technology

[0025]1.本发明不涉及超临界干燥,无昂贵设备要求。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117624713B_ABST
    Figure CN117624713B_ABST
Patent Text Reader

Abstract

The application discloses a high-temperature-resistant ablative phenolic aerogel and a preparation method thereof. The method uses a mixed solution of a phenolic sol and a nanocrystal dispersion solution as a sol reaction solution. In a gradient temperature sol-gel and aging process, the phenolic can be synchronously sol-gel with the nanocrystal, and finally a double-skeleton structure with the nanocrystal as a lapping structure and the phenolic as a coating structure can be formed. The double-skeleton structure effectively improves the overall strength of the aerogel and ensures the resistance to capillary force in the aerogel skeleton in a normal-pressure drying process. The application has the characteristics of simple operation, no need for supercritical drying and suitability for industrial production, and is expected to be applied to micro-ablation heat-proof materials in the field of light-weight heat protection.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a high-temperature ablation resistant phenolic aerogel and its preparation method, belonging to the field of aerogel preparation, and can be applied to micro-ablation protection / insulation materials in the field of lightweight thermal protection. Background Technology

[0002] Phenolic resins possess excellent flame retardancy and ablation resistance, making them widely used in building materials, aerospace, and weaponry. Phenolic aerogels, as derived nanoporous materials, not only have lower density but also better thermal insulation properties, making them a significant improvement in aircraft performance when used as ablation insulation materials. With the increasing operational speed of various aircraft, phenolic aerogels, as thermal protection materials, will face increasingly harsh aerodynamic and thermal environments during aircraft operation. Traditional phenolic aerogels will undergo severe ablation and pyrolysis, leading to volume shrinkage, cracking, and even fragmentation of the thermal protection layer, thermal insulation failure, and aerodynamic shape damage, all of which are detrimental to the normal operation of the aircraft. Therefore, improving the ablation shape retention of phenolic aerogels and achieving integrated thermal protection / insulation is a key technology in the field of aircraft thermal protection.

[0003] Yu Zhi-Long et al. used chitosan as a template and phenol, formaldehyde, and tetraethyl orthosilicate as raw materials. Through hydrolysis and condensation reactions, and with the aid of supercritical drying, they obtained phenolic-silica dual-network hybrid aerogels, which effectively improved the ablation shape retention of phenolic aerogels (Yu ZL, Yang N, Apostolopoulou-Kalkavoura V, et al. Fire-retardant and thermally insulation phenolic-silica aerogels[J]. Angewandte Chemie International Edition, 2018, 57(17):4538-4542.). However, this method requires the aid of a template and depends on expensive supercritical drying, which is not conducive to large-scale production and application. Shi Jianjun et al. used linear phenolic resin and tetraethyl orthosilicate as raw materials, and obtained phenolic-silica dual-network hybrid aerogels through hydrolysis, condensation reaction and atmospheric pressure drying, which effectively improved the strength and thermal stability of the phenolic aerogel network structure (Shi Jianjun, Kong Lei, Zuo Xiaobiao et al. Preparation and properties of phenolic / SiO2 dual-system gel network structure hybrid aerogels [J]. Acta Polymerica Sinica, 2018, (10): 1307-1314.). Although a series of advances have been made in the preparation of phenolic-silica hybrid aerogels, due to the poor high-temperature stability of silica aerogels themselves, sintering begins at around 800℃, which affects the thermal insulation performance and cannot meet the requirements of high-speed aircraft for integrated thermal protection / insulation materials.

[0004] Alumina nanocrystalline aerogels are a type of aerogel formed by the three-dimensional stacking of nanostructure units such as nanosheets and nanorods. Compared with traditional aerogels formed by the stacking of nanoparticles, nanocrystalline aerogels have excellent anti-sintering ability (CN110282958A). In addition, alumina has a melting point of over 2000℃, and the service temperature of alumina nanocrystalline aerogels can reach over 1400℃ (Zhang E, Zhang W, Lv T, et al. Insulating and robust ceramic nanorod aerogels with high-temperature resistance over 1400℃[J].ACS Applied Materials & Interfaces, 2021, 13(17):20548-20558.). However, the preparation of alumina nanocrystalline aerogels currently relies on expensive supercritical equipment, limiting their large-scale application (Liu F, He C, Jiang Y, et al. Carbonlayer encapsulation strategy for designing multifunctional core-shell nanorodaerogels as high-temperature thermal superinsulators[J]. Chemical Engineering Journal, 2023, 455: 140502.). Therefore, achieving the organic-inorganic hybridization of phenolic resin and alumina nanocrystals under normal pressure drying conditions holds promise for obtaining high-performance integrated heat-insulating and protective materials that meet the requirements of high-speed aircraft. Summary of the Invention

[0005] To improve the heat protection / insulation performance and preparation method of the above-mentioned modified phenolic-silica hybrid aerogel, this invention provides a high-temperature ablation resistant shaped phenolic aerogel and its preparation method, realizing the organic-inorganic hybridization of phenolic resin and alumina nanocrystals, making up for the defects of insufficient shape and heat insulation caused by silica sintering in phenolic-silica hybrid aerogel, and meeting the requirements of long-duration high-speed aircraft for integrated heat protection / insulation materials.

[0006] To achieve the above objectives, the technical solution adopted by the present invention is as follows:

[0007] In a first aspect, the present invention provides a method for preparing a high-temperature ablation-resistant phenolic aerogel, comprising the following steps:

[0008] Phenolic sol was added to alumina nanocrystal dispersion and stirred until homogeneous to obtain sol reaction solution;

[0009] The sol reaction solution was subjected to sol-gelation and aging through gradient heating to obtain a wet gel.

[0010] The wet gel was dried at room temperature and pressure to obtain a phenolic-alumina nanocrystalline hybrid aerogel.

[0011] Furthermore, the alumina nanocrystal dispersion is prepared using the following steps:

[0012] (1) Disperse alumina nanopowder and acidic solution evenly in water to obtain a dispersion;

[0013] (2) Place the dispersion in (1) in a sealed container and then place it in a high-temperature oven to react and obtain the nanocrystalline dispersion stock solution;

[0014] (3) Mix the nanocrystalline dispersion stock solution in (2) with silica sol and catalyst evenly to obtain nanocrystalline dispersion.

[0015] Furthermore, the alumina nanoparticles have a particle size of 10–200 nm.

[0016] Furthermore, the acidic solution may be one or more acids such as hydrochloric acid, glacial acetic acid, and sulfuric acid.

[0017] Furthermore, the phenolic sol is obtained by mixing and dissolving phenol and aldehyde; the phenol used can be one or more of phenols such as phenol, resorcinol, and naphthol; the aldehyde used can be one or more of aldehydes such as formaldehyde, acetaldehyde, and furfural.

[0018] Furthermore, the mass of the phenolic sol is 20% to 60% of the mass of the alumina nanocrystal dispersion.

[0019] Furthermore, the step of heating and curing the sol-gel reaction solution through a gradient temperature increase includes: loading the sol-gel reaction solution into a reaction vessel, then placing the reaction vessel in an oven, and heating and curing it through a gradient temperature increase, i.e., performing sol-gelation and aging. The temperature range for sol-gelation and aging is 50℃~120℃.

[0020] Furthermore, the step of drying the wet gel at room temperature and pressure includes: cooling the reaction vessel, removing the wet gel, and drying it at room temperature and pressure until its mass does not change, ultimately obtaining a phenolic-alumina nanocrystalline hybrid aerogel.

[0021] Secondly, the present invention provides a high-temperature resistant ablation-resistant phenolic aerogel prepared by the above method.

[0022] In the above technical solution, the viscosity of the nanocrystalline dispersion stock solution is relatively high. After being mixed evenly with silica sol and catalyst, the viscosity is significantly reduced.

[0023] The principle of this invention is as follows: In the sol-gel reaction solution, small phenolic sol molecules can be adsorbed onto the surface of nanocrystals. During gradient temperature heating, the phenolic sol can simultaneously gel with the nanocrystals, ultimately forming a dual-framework structure with nanocrystals as the lap joint structure and phenolic sol as the coating structure. This dual-framework structure effectively improves the overall strength of the aerogel and ensures the resistance of the aerogel framework to capillary forces during the atmospheric pressure drying process.

[0024] Due to the application of the above-mentioned technical solution, the present invention has the following advantages compared with the prior art:

[0025] 1. This invention does not involve supercritical drying and does not require expensive equipment.

[0026] 2. This invention introduces an alumina nanocrystal three-dimensional structure into the phenolic aerogel, which greatly improves the ablation shape retention of the phenolic aerogel.

[0027] 3. This invention achieves an organic-inorganic hybridization of phenolic resin and alumina nanocrystals, resulting in a high-performance integrated heat-insulating / protective material. The high-temperature ablation-resistant phenolic aerogel prepared by this invention can be applied to micro-ablation heat-insulating / protective materials in the field of lightweight thermal protection. Attached Figure Description

[0028] Figure 1 This is a schematic diagram of the preparation steps of the phenolic-alumina nanocrystal hybrid aerogel in Example 1;

[0029] Figure 2 This is a photograph of the phenolic-alumina nanocrystalline hybrid aerogel in Example 1;

[0030] Figure 3 This is a scanning electron microscope image of the phenolic-alumina nanocrystalline hybrid aerogel in Example 1. Detailed Implementation

[0031] The following is in conjunction with the appendix Figures 1-3 The present invention will be further described in conjunction with the embodiments:

[0032] Example 1

[0033] A high-temperature ablation-resistant phenolic aerogel and its preparation method thereof, comprising the following steps:

[0034] (1) Weigh 60g of alumina nanoparticles and disperse them in 500mL of water. Then add 5mL of concentrated hydrochloric acid to the dispersion and stir until homogeneous.

[0035] (2) Place the dispersion from (1) in a sealed container and then place it in a high-temperature oven at 240°C for 4 hours to obtain the nanocrystalline dispersion stock solution.

[0036] (3) Add 20g of silica solution with a solid content of 4% and 2g of NH4F solution with a concentration of 1mol / L to the nanocrystal dispersion obtained in (2), stir evenly, and obtain nanocrystal dispersion.

[0037] (4) Weigh 55g of resorcinol and 96g of furfural and stir to dissolve to obtain phenolic sol. Then add the phenolic sol to the nanocrystal dispersion in (3) and stir evenly to obtain sol reaction solution.

[0038] (5) The reaction solution obtained in (4) is loaded into the reaction vessel, and then the reaction vessel is placed in the oven and heated at 50°C for 1 day, 90°C for 1 day, and 120°C for 1 day to carry out sol-gel and aging.

[0039] (6) After cooling the reaction vessel in (5), take out the wet gel and dry it at room temperature and pressure until the mass does not change, and finally obtain phenolic-alumina nanocrystalline hybrid aerogel.

[0040] The final phenolic-alumina nanocrystalline hybrid aerogel had a density of 0.50 g / cm³. 3 The drying shrinkage rate is 12%, and the specific surface area is 132 m². 2 / g.

[0041] Figure 1 This is a schematic diagram of the preparation steps for phenolic-alumina nanocrystalline hybrid aerogel.

[0042] Figure 2 This is a photograph of the phenolic-alumina nanocrystalline hybrid aerogel. It can be seen that the aerogel did not crack during the atmospheric pressure drying process.

[0043] Figure 3 This is a scanning electron microscope (SEM) image of a phenolic-alumina nanocrystal hybrid aerogel. It can be seen that the alumina nanocrystals exhibit a rod-like structure, with phenolic resin and nanocrystals uniformly distributed. No "island" phase separation structure is observed. Particulate phenolic aerogel particles are visible on the surface of the nanocrystals.

[0044] Example 2

[0045] A high-temperature ablation-resistant phenolic aerogel and its preparation method thereof, comprising the following steps:

[0046] (1) Weigh 60g of alumina nanoparticles and disperse them in 500mL of water. Then add 8mL of glacial acetic acid to the dispersion and stir until homogeneous.

[0047] (2) Place the dispersion from (1) in a sealed container and then place it in a high-temperature oven at 240°C for 4 hours to obtain the nanocrystalline dispersion stock solution.

[0048] (3) Add 20g of silica solution with a solid content of 4% and 2g of NH4F solution with a concentration of 1mol / L to the nanocrystal dispersion obtained in (2), stir evenly, and obtain nanocrystal dispersion.

[0049] (4) Weigh 110g of resorcinol and 162g of formaldehyde (formalin solution) and stir to dissolve to obtain phenolic sol. Then add the phenolic sol to the nanocrystal dispersion in (3) and stir evenly to obtain sol reaction solution.

[0050] (5) The reaction solution obtained in (4) is loaded into the reaction vessel, and then the reaction vessel is placed in the oven and heated at 50°C for 1 day, 70°C for 1 day, and 90°C for 1 day to carry out sol-gel and aging.

[0051] (6) After cooling the reaction vessel in (5), take out the wet gel and dry it at room temperature and pressure until the mass does not change, and finally obtain phenolic-alumina nanocrystalline hybrid aerogel.

[0052] The final phenolic-alumina nanocrystalline hybrid aerogel had a density of 0.43 g / cm³. 3 The drying shrinkage rate is 13%, and the specific surface area is 164 m². 2 / g.

[0053] Example 3

[0054] A high-temperature ablation-resistant phenolic aerogel and its preparation method thereof, comprising the following steps:

[0055] (1) Weigh 60g of alumina nanoparticles and disperse them in 500mL of water. Then add 5mL of concentrated hydrochloric acid to the dispersion and stir until homogeneous.

[0056] (2) Place the dispersion from (1) in a sealed container and then place it in a high-temperature oven at 240°C for 4 hours to obtain the nanocrystalline dispersion stock solution.

[0057] (3) Add 20g of silica solution with a solid content of 4% and 2g of NH4F solution with a concentration of 1mol / L to the nanocrystal dispersion obtained in (2), stir evenly, and obtain nanocrystal dispersion.

[0058] (4) Weigh 110g resorcinol, 81g formaldehyde (formalin solution) and 48g furfural and stir to dissolve to obtain phenolic sol. Then add the phenolic sol to the nanocrystal dispersion in (3) and stir evenly to obtain sol reaction solution.

[0059] (5) The reaction solution obtained in (4) is loaded into the reaction vessel, and then the reaction vessel is placed in the oven and heated at 50°C for 1 day, 90°C for 1 day, and 120°C for 1 day to carry out sol-gel and aging.

[0060] (6) After cooling the reaction vessel in (5), take out the wet gel and dry it at room temperature and pressure until the mass does not change, and finally obtain phenolic-alumina nanocrystalline hybrid aerogel.

[0061] The final phenolic-alumina nanocrystalline hybrid aerogel had a density of 0.46 g / cm³. 3 The drying shrinkage rate is 12%, and the specific surface area is 148 m². 2 / g.

[0062] The specific embodiments of the present invention disclosed above are intended to help understand the content of the present invention and to implement it accordingly. Those skilled in the art will understand that various substitutions, changes, and modifications are possible without departing from the spirit and scope of the present invention. The present invention should not be limited to the content disclosed in the embodiments of this specification; the scope of protection of the present invention is defined by the claims.

Claims

1. A method for preparing a high-temperature ablation-resistant phenolic aerogel, characterized in that, Includes the following steps: Phenolic sol was added to alumina nanocrystal dispersion and stirred until homogeneous to obtain sol reaction solution; The sol reaction solution was subjected to sol-gelation and aging through gradient heating to obtain a wet gel. The wet gel was dried at room temperature and pressure to obtain a phenolic-alumina nanocrystalline hybrid aerogel. The alumina nanocrystal dispersion was prepared using the following steps: Alumina nanoparticles and an acidic solution are dispersed evenly in water to obtain a dispersion. The dispersion was placed in a sealed container and then placed in a high-temperature oven to react and obtain a nanocrystalline dispersion stock solution. The nanocrystalline dispersion stock solution was mixed evenly with silica sol and catalyst to obtain the nanocrystalline dispersion solution; The mass of the phenolic sol is 20% to 60% of the mass of the alumina nanocrystal dispersion.

2. The method according to claim 1, characterized in that, The alumina nanoparticles have a particle size of 10-200 nm; the acidic solution is at least one of hydrochloric acid, glacial acetic acid, and sulfuric acid.

3. The method according to claim 1, characterized in that, The phenolic sol is obtained by mixing and dissolving phenol and aldehyde.

4. The method according to claim 3, characterized in that, The phenol is at least one of phenol, resorcinol, and naphthol; the aldehyde is at least one of formaldehyde, acetaldehyde, and furfural.

5. The method according to claim 1, characterized in that, The step of performing sol-gel and aging by gradient heating of the sol-reaction solution includes: loading the sol-reaction solution into a reaction vessel, then placing the reaction vessel into an oven, and performing sol-gel and aging by gradient heating.

6. The method according to claim 5, characterized in that, The process involves gradient heating to induce sol-gelation and aging, wherein the temperature range for sol-gelation and aging is 50℃~120℃.

7. The method according to claim 6, characterized in that, The process of drying the wet gel at room temperature and pressure includes: cooling the reaction vessel, removing the wet gel, and drying it at room temperature and pressure until its mass does not change, ultimately obtaining a phenolic-alumina nanocrystalline hybrid aerogel.

8. High-temperature ablation resistant phenolic aerogel prepared by the method according to any one of claims 1 to 7.

Citation Information

Patent Citations

  • High-temperature-resistant heteromorphic nanocrystalline aerogel material and preparation method thereof

    CN110282958A

  • Organic-inorganic double network structure phenolic aldehyde / alumina aerogel composite material and preparation method thereof

    CN109200955A

  • Polymeric aerogel composite and synthesis by ambient and freeze-drying`

    US20210206926A1